Complement deficiency and disease. Issue 9 (21st May 2008) - Unsworth, D J
Abstract : There are approximately 30 serum complement proteins (15% of the globulin fraction), excluding cell surface receptors, and regulatory proteins. Many are manufactured in the liver, and reduced complement is a feature of severe liver failure. Complement proteins contribute to the acute phase response, and high levels are seen in chronic untreated inflammation (eg, rheumatoid arthritis). Once activated, complement is strongly pro-inflammatory. Indeed, almost half of the complement system proteins/receptors play regulatory roles, reflecting the importance of controlling inappropriate activation. This review focuses on disease states arising as a direct consequence of complement deficiency or dysfunction.